Recent Trends and Future Directions on Value Addition of Irish Potato (Solanum Tuberosum L.) among Smallholder Farmers - Jacinta Mlaviwa; Edward Missanjo (Emerging Science Journal, 2019)
Irish potato (Solanum tuberosum L.) value addition has the potential to enhance food security, household income and nutrition. This cross-sectional study was, therefore, conducted to examine value addition of Irish potato among smallholder farmers in Ntcheu, central Malawi. Data was collected using a standard structured questionnaire administered through face-to-face interviews. The results revealed that there were significant differences (X2=103.3; p<0.001) on value addition techniques practiced by farmers. The following value addition techniques were identified: chips (65%), packaging (27.5%), crisps (25%), grading (12.5%), salad (5%), baking (5%), soup (2.5%) and grounding into flour (2.5%). It was noted that factors influencing Irish potato value addition among farmers significantly (X2=8.020; p=0.046) differed. The majority (70%) of the farmers were influenced by knowledge of value addition, followed by ready markets for products (57.5%), while a few were influenced by capital (45.5%) and availability of value addition equipment (40.0%). The study further revealed that education level and group participation significantly (P<0.05) influenced Irish potato value addition technique practices. Farmers with secondary education level or above and those in Irish potato group production are involved in diverse value addition techniques. Encouraging farmer group formation, access to loans to buy value addition equipment, linking farmers with supermarkets, and farmer’s exposure to field days and workshops are the strategies identified to promote effective Irish potato value addition among smallholder farmers.